Michael K. Evans. Macroeconomic activity theory, forecasting, and control : an econometric approach. Nueva York : Harper & Rowe, 1969. 627 p. - Solís M., Leopoldo (Estudios Demográficos y Urbanos, 1970)
MICHAEL K. EVANS, Macroeconomic Activity Theory, Foreeasting, and Control. An Eoonametric Approach. Nueva York, Harper & Rowe, 1969.